Submission Title: Hubungan Tingkat Pengetahuan Ibu tentang Pemberian Nutrisi yang Tepat dengan Status Gizi Berdasarkan Grafik KMS pada Balita di Desa Batukerbuy Kecamatan Pasean Kabupaten Pamekasan - Nur Jayanti (Ovary Midwifery Journal, 2019)
Nutrition is a process of organisms using food consumed normally through the process of absorption, transportation,storage, metabolism and expenditure of substances that are not used to maintain life, growth and normal function oforgans and produce energy. One of the nutritional status of children under five is influenced by factors of socioeconomic conditions, including maternal education, employment of mothers, number of children, knowledge andparenting, as well as the overall economic condition of parents. This research was conducted to find out whetherthere was a relationship between family socio-economic conditions on the nutritional status of children under five.Whereas in the districts of July 2016, there were 163 children under five. There were 7 children who experiencedmalnutrition, and 21 children who experienced malnutrition and 135 children experienced good nutrition (82.82%).The purpose of this study was to determine the relationship of the level of knowledge of mothers about the provisionof proper nutrition with nutritional status based on Kms graphs on toddlers in Batukerbuy Village, PaseanSubdistrict, Pamekasan Regency in 2018. This research is a kind of correlative description with a quantitativeapproach. The study was conducted in Batukerbuy village, Pasean Subdistrict, Pamekasan Regency, from March toMay 2018. Subsequent collection using Simple Random Sampling with a total sample of 126 mothers who havechildren under five. The dependent variable is the nutritional status of children based on the KMS graph and thedependent variable is the level of knowledge of mothers in providing nutrition. The dependent and independentvariables are measured using questionnaires and KIA books. Data analysis using the Spearman rank rank test. From the analysis of partial test obtained value  value = 0,026 <  = 0,05. means that there is a relationship betweenmother's knowledge about providing appropriate nutrition with nutritional status based on KMS in infants. This issupported by mother's knowledge, information and experience. Nutritional status of toddlers is strongly influencedby the knowledge of mothers about providing appropriate nutrition, so it is expected that the community, especiallymothers who have toddlers can increase knowledge from counseling and information about nutrition from healthcenters and other media.